Situs inversus totalis: Unique presentation with oesophageal atresia and distal trachea-oesophageal fistula - Rahaf Al- Rayiqi; Ahmad Alawi; Aisha Gabra; Husain Sondogji (Elsevier, 2023)
Introduction Oesophageal atresia OA with distal trachea-oesophageal fistula TOF is the most common type of OA. OA affects 1 in 3000 live-born infants. Situs Inversus Totalis is a rare anomaly with a total right-to-left transposition of the thoracoabdominal organs. The incidence of SIT is 0.01%. An Association between OA and TOF with SIT is extremely rare. Few studies on this association have been published in English literature.Case presentation A full-term female baby started to have excessive salivation and regurgitation of the first feed and developed choking and respiratory distress on the first day of life. Attempt to pass OGT failed. Plain chest radiographs demonstrated a coiled OGT in the upper oesophageal pouch and distal aeration, suggesting oesophageal atresia with distal TOF and dextrocardia. Abdominal ultrasonography confirmed the diagnosis of SIT. Cardiac echography showed a left-sided aortic arch, atrioventricular septal defect (AVSD), and double patent ductus arteriosus (PDA). An extra-pleural left thoracotomy was done, revealing a left-sided azygous vein and a left-sided aortic arch. After ligating the TOF, a primary end-to-end oesophageal anastomosis was performed. A trans-anastomotic tube was placed. A chest tube was inserted. On the seventh day, a contrast oesophagogram was done and showed no leakage. She had an uneventful recovery and was discharged in good condition.Conclusion left thoracotomy seems to be a reasonable approach for TOF with SIT and a left-sided aortic arch to avoid possible complications. Any associated anomalies should be addressed to prevent potential complications.